How Can My Poem Be True? - John L. Hoben (Art/Research International, 2021)
How can a poem be true? This autoethnographic study uses poetic inquiry to explore the boundaries between fiction and reality within poetic experience. A series of poems composed during, and about, the current COVID-19 pandemic, provides a means of understanding the experience of having one’s everyday reality overturned by crisis. A central theme of the author’s poems and accompanying reflections is how art can be used to explore psychological experiences, such as melancholia and depression, and, in turn how the experience of suffering can be used to facilitate artistic expression. Using poetic inquiry, the author examines the complex interplay between speaker and authorial intention, fiction and truth, text and the performance of writing, reading, and poetic interpretation.